Strong C iv emission from star-forming galaxies: a case for high Lyman continuum photon escape. Issue 1 (26th September 2022) - Saxena, A; Cryer, E; Ellis, R S; Pentericci, L; Calabrò, A; Mascia, S; Saldana-Lopez, A; Schaerer, D; Katz, H; Llerena, M; Amorín, R
ABSTRACT: Finding reliable indicators of Lyman continuum (Ly C) photon leakage from galaxies is essential in order to infer their escape fraction in the epoch of reionization, where direct measurements of Ly C flux are impossible. To this end, here we investigate whether strong C iv λλ1548, 1550 emission in the rest-frame UV spectra of galaxies traces conditions ripe for ample production and escape of Ly C photons. We compile a sample of 19 star-forming galaxies in the redshift range z = 3.1–4.6 from the VANDELS survey that exhibit strong C iv emission, producing a stacked spectrum where all major rest-UV emission lines are clearly detected. Best-fitting spectral energy distribution models containing both stellar and nebular emission suggest the need for low stellar metallicities (Z=0.1–0.2 Z_ ), young stellar ages ((age yr^-1) = 6.1–6.5 ), a high ionization parameter (log U = −2) and little to no dust attenuation ( E ( B − V ) = 0.00–0.01). However, these models are unable to fully reproduce the observed C iv and He ii line strengths. We find that the Ly α line in the stacked spectrum is strong and peaks close to the systemic velocity, features that are indicative of significant Ly C photon leakage along the line of sight. The covering fractions of low-ionization interstellar absorption lines are also low, implying Ly C escape fraction in the range ≈0.05–0.30, with signatures of outflowing gas. Finally, C iv /C iii ] ratios of >0.75 for a subset of individual galaxies with reliable detections of both lines are also consistent with physical conditions that enable significant Ly C leakage. Overall, we report that multiple spectroscopic indicators of Ly C leakage are present in the stacked spectrum of strong C iv emitting galaxies, potentially making C iv an important tracer of Ly C photon escape at z > 6.